SURVEY ON HUMAN COMPUTER INTERACTION PRINCIPLES ON SUBSCRIPTION VIDEO ON DEMAND PROVIDER - Christine; Deli, Deli (ZONAsi: Jurnal Sistem Informasi, 2024)
Human Computer Interaction is the processes or activities carried out by humans interacting with computers, which provide feedback through an interface to obtain expected results. This research is to compare the usability of Netflix and Disney+ Hotstar based on its user experience by using the Human Computer Interaction Principles (HCI). User Experience is described as experiences related to reactions, perceptions, behaviors, emotions and thoughts of users when using the system. This research will be conducted by using quantitative research through User Experience Questionnaire (UEQ). There are two UEQ, one for Netflix’s users and one for Disney+ Hotstar users. A total of 400 respondents, who were 200 Netflix users, and a total of 200 respondents, who were Disney+ Hotstar users, provided data for the study. To ensure the robustness of the collected data, rigorous validity and reliability tests were conducted using the Statistical Package for the Social Sciences (SPSS). The results of the analysis show that all data that has been obtained can be categorized as valid or accepted.